FISIOTERAPI FASE II ATRIAL SEPTAL DEFECT CONGENITAL : CASE REPORT - Hafizhah Putri Ilma Darojati; Azmi Fitra Mitrah Riyanto; Agus Widodo; I Putu Aditya Pratama (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Atrial Septal Defect (ASD) is a congenital heart disease or abnormality caused by a hole in the right and left atrial partition so that the blood mixes. Most ASDs do not show signs and symptoms, but patients generally experience symptoms related to decreased functional capacity, including shortness of breath during activity. ASD valve closure surgery is a safe maintenance procedure and has an impact on low mortality rates. The phase II physiotherapy program in this case aims to determine the effect of aerobic exercise, treadmill and ergocycle interventions on increasing functional capacity. This study is a case report on subjects with post surgical Arterial Septal Defect closure conditions with a phase II rehabilitation program in the form of aerobic exercise, treadmill and ergocycle for 5 therapy sessions. Next, vital signs were measured, blood pressure, heart rate (HR), SpO2 quality, Borg Scale shortness of breath measurements at each therapy session and functional capacity (6MWT). The results showed stable blood pressure and HR, decreased shortness of breath, and increased functional capacity or METs results. Keywords: Atrial Septal Defect; Physiotherapy; Functional capacity; Phase II rehabilitation